The influence of risk perception and safety concerns on tourist decision planning: A case study on the post-tsunami Sunda straits - Muharni, Yusraini; Wulan, Elis Ratna; Ulfah, Maria; Hartono, Hartono; Muttaqien, Ade Irman Saeful; Wulandari, Anting (Universitas Sultan Ageng Tirtayasa, 2024)
Risk perception directly influences tourists' involvement in trip planning, particularly in seeking information before and during their trips. Natural disasters like tsunamis can pose significant risks to tourist safety, ranging from minor injuries to severe harm and even death. This study investigates how risk perception and safety concerns influence tourists' decision-making, with a focus on post-tsunami tourism in the Sunda Straits area, which was severely impacted by the 2018 tsunami caused by the eruption of Mount Anak Krakatau. A sample of 116 domestic tourists was surveyed to understand the relationship between risk perception, safety concerns, and tourist decision planning. The results reveal that risk perception is a critical factor in shaping safety concerns and, subsequently, tourists' decisions. This research offers insights into how disaster risk management in tourism can influence recovery strategies. Practical implications include the need for improved risk communication and enhanced safety measures to restore tourist confidence in the region.